Comprehensive Physiology 2011
DOI: 10.1002/cphy.c100034
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Pathological Angiogenesis in the Adult Pulmonary Circulation

Abstract: Angiogenesis occurs during growth and physiological adaptation in many systemic organs, for example, exercise-induced skeletal and cardiac muscle hypertrophy, ovulation, and tissue repair. Disordered angiogenesis contributes to chronic inflammatory disease processes and to tumor growth and metastasis. Although it was previously thought that the adult pulmonary circulation was incapable of supporting new vessel growth, over that past 10 years new data have shown that angiogenesis within this circulation occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 408 publications
0
10
0
Order By: Relevance
“…The increase in total capillary endothelial surface area in the hypoxic lung observed in these experiments suggests that capillary angiogenesis had taken place. We observed that the harmonic mean thickness of the gas‐exchange membrane (including both tissue and plasma components) was not significantly increased in the hypoxic mouse lung, which taken together with the increased surface area, suggests that the capillary and epithelial changes induced by hypoxia would have increased the membrane diffusing capacity for oxygen (Weibel, 1999; McLoughlin & Keane, 2011). Such an increase would be a beneficial adaptive advantage in a hypoxic environment, such as that at high altitude.…”
Section: Discussionmentioning
confidence: 89%
“…The increase in total capillary endothelial surface area in the hypoxic lung observed in these experiments suggests that capillary angiogenesis had taken place. We observed that the harmonic mean thickness of the gas‐exchange membrane (including both tissue and plasma components) was not significantly increased in the hypoxic mouse lung, which taken together with the increased surface area, suggests that the capillary and epithelial changes induced by hypoxia would have increased the membrane diffusing capacity for oxygen (Weibel, 1999; McLoughlin & Keane, 2011). Such an increase would be a beneficial adaptive advantage in a hypoxic environment, such as that at high altitude.…”
Section: Discussionmentioning
confidence: 89%
“…In the lung, microvascular endothelial cells proliferate approximately twice as fast as macroarterial endothelial cells (16) Moreover, PVEC-derived angiocrine signals might facilitate regenerative alveologenesis as shown in rats subjected to unilateral pneumonectomy (9). The increased capillary bed with accompanied growth of the alveolar epithelium could be an important contribution for adapting to hypoxia by increasing the diffusing capacity of the lung thanks to an expansion of the effective surface area of the alveolar gas exchange membrane (18). Thus the robust proliferation of PVECs observed in this study might play a beneficial role in the adaptive response to chronic hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis occurs in the pulmonary circulation during physiological adaptation and/or pathological mechanisms in lung disease. 26,27 Indeed, hypoxia is a condition of decreased O 2 levels that is seen in high altitudes and many respiratory diseases. 6 It can stimulate lung angiogenesis in adults, 26,28 through many factors or cytokines.…”
Section: Discussionmentioning
confidence: 99%